Trends in Spine Surgery Training During Neurological and Orthopaedic Surgery Residency: A 10-Year Analysis of ACGME Case Log Data. (20th November 2019) - Pham, Martin H.; Jakoi, Andre M.; Wali, Arvin R.; Lenke, Lawrence G.
Abstract : Background: Spine surgery training in the United States currently involves residency training in neurological or orthopaedic surgery. Because of different core residency surgical requirements, the volume of spine surgery procedures may vary between the 2 residencies. Methods: We reviewed the Accreditation Council for Graduate Medical Education resident case logs for both orthopaedic surgery and neurological surgery for exposure to spine surgery procedures for the graduating years of 2009 to 2018. Results: The average number of spine surgery procedures performed during that 10-year period was 433.8 for neurosurgery residents and 119.5 for orthopaedic surgery residents (p < 0.01). From 2009 to 2018, neurosurgery residents saw an increase of 26.5% in spine surgery procedures (from 389.6 to 492.9 procedures), whereas orthopaedic surgery residents saw a decrease of 41.3% (from 141.1 to 82.8 procedures). The 10-year average percentage of total spine procedures among all total surgical cases was 33.5% for neurosurgery residents compared with 6.2% for orthopaedic surgery residents (p < 0.01). This percentage decreased for both neurosurgery residents (35.8% in 2009 to 31.3% in 2018) and orthopaedic surgery residents (7.2% in 2009 to 4.9% in 2018). Neurosurgical residents performed 3.6 times more total spine procedures than orthopaedic surgery residents on average, a number that increased from 2.8-fold in 2009 to 6.0-fold in 2018. Conclusions: The case volume of spine surgery procedures varies greatly, with higher rates for neurological surgery and lower rates for orthopaedic surgery residencies, with an increasing discrepancy over time. Although case volume alone cannot solely determine quality of training, it is one measure to assess opportunities to develop optimal spine education around a certain accepted volume of surgical patient care. Not accounted for here are additional postgraduate spine cases performed by orthopaedic surgery residents who pursue spine fellowship training (an additional 300 to 500 cases). The results described herein may help to explore the various needs of and differences between residents seeking to pursue careers in spine as well as the role of spine surgery fellowships currently and in the future.